Indigenism and social classes - Deustua Carvallo, José (1979)
A book is above all an open door to a new world of knowledge without borders. Reviewing it implies discussing it to, in some way, make that world more accessible and delimit its borders. The recent publication of the collective book by Degregori, Valderrama, Alfageme and Francke; INDIGENISMO, SOCIAL CLASSES AND NATIONAL PROBLEM, therefore, supposes starting this process of critical reading that every good book creates within the reading public.